Regulation and risk occupational health and safety on the railways - Hutter, Bridget M. (Oxford University Press, 2001)
This study examines the impact of a system of enforced self-regulation on the corporate life of British Railways. The book raises important questions about how workplace risks are managed and what influence the law can have.
Keywords: Railroads -- Great Britain -- Safety measures.; Railroads -- Employees -- Health and hygiene -- Great Britain.; Risk management -- Great Britain.; Railroad law -- Great Britain.; Great Britain.; USA.; elektronické knihy; electronic books